Senior Citizens' Health and Social Services in Cebu City - Toring, Kimberly Cui Nuevo; Toring, Eugene Escalona; Nuevo, Jonathan Obinque; Gabuya, Patricio G.; Maming, Jimmy Bernabe (Future Science / FSH-PH Publications, 2021)
Senior citizens are an important sector in society. Some began their new career during the middle age and many continued a long legacy of productivity and passionate social service living a life of commitment. The aims of the study is to assess the senior citizen’s health and social services in Cebu City. The study uses quantitative and qualitative methods. A statistical computation was used to achieve an acceptable accuracy of findings and the qualitative research double-checks the quantitative research. Furthermore, the qualitative method was used to measure the data since it allowed the participants to give in-depth, detailed answers by personal interview. The Researchers explored the participant’s answers, thus clearing any ambiguity before analyzing and publishing the collected data. The study revealed that the level of implementation of social services for senior citizens was well implemented; The level of perception of health services for senior citizens were provided; The management of senior citizens office has the biggest financial appropriation; that there was no correlation between social services and the perception level since both were labeled not significant. To address the gap a substantial budget shall be allocated to the sixty (60) barangays of Cebu City to be incorporated in OSCA budget. A development plan was proposed as the output of the study.